2000
DOI: 10.1094/mpmi.2000.13.7.742
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of a Cyclic Peptide Synthetase Gene from Alternaria alternata Apple Pathotype Whose Product Is Involved in AM-Toxin Synthesis and Pathogenicity

Abstract: Afternaria afternata apple pathotype causes Alternaria blotch of susceptible apple cultivars through the production of a cyclic peptide host-specific toxin, AM-toxin. PCR (polymerase chain reaction), with primers designed to conserved domains of peptide synthetase genes, amplified several products from A. alternata apple pathotype that showed high similarity to other fungal peptide synthetases and were specific to the apple pathotype. Screening of a Lambda Zap genomic library with these PCR-generated probes id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
132
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(133 citation statements)
references
References 53 publications
0
132
0
1
Order By: Relevance
“…In Alternaria alternata plant pathogens (37), we have shown that all strains of the A. alternata pathotypes harbor small extra chromosomes of less than 1.7 Mb, whereas nonpathogenic isolates do not have these small chromosomes (5). A cyclic peptide synthetase gene, AMT, which is involved in host-specific AM toxin biosynthesis of the apple pathotype of A. alternata, was located on a small chromosome of 1.1 to 1.7 Mb, depending on the strain (22,23). The AF toxin biosynthesis gene cluster was also present on a single small chromosome of 1.05 Mb in the strawberry pathotype of A. alternata (18).…”
mentioning
confidence: 99%
“…In Alternaria alternata plant pathogens (37), we have shown that all strains of the A. alternata pathotypes harbor small extra chromosomes of less than 1.7 Mb, whereas nonpathogenic isolates do not have these small chromosomes (5). A cyclic peptide synthetase gene, AMT, which is involved in host-specific AM toxin biosynthesis of the apple pathotype of A. alternata, was located on a small chromosome of 1.1 to 1.7 Mb, depending on the strain (22,23). The AF toxin biosynthesis gene cluster was also present on a single small chromosome of 1.05 Mb in the strawberry pathotype of A. alternata (18).…”
mentioning
confidence: 99%
“…In addition to structural diversity, nonribosomal peptides have a broad spectrum of biological activities, some of which have been useful in medicine, agriculture, and biological research (24,37,40,47). Products made by nonribosomal peptide synthetases or nonribosomal peptide synthetase/polyketide synthase hybrid enzymes include well-known antibiotics (penicillin, erythromycin, and vancomycin), immunosuppressants (cyclosporin and rapamycin), antitumor agents (actinomycin, bleomycin, and epothilone) (39,47), and toxins involved in pathogenesis (HC-toxin, enniatin, AM-toxin, and probably victorin) (17,22,32,38,48,49).…”
mentioning
confidence: 99%
“…Some proposed activities include roles as signal molecules for coordination of growth and differentiation (16,21,28,35), as aids in the breakdown of cellular metabolic products (9), as defense compounds that kill competing microorganisms (46), as siderophores to assist in iron uptake (5), and as virulence effectors (17,22,32,38).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several A. alternata pathotypes produce toxic, host-specific secondary metabolites that are pathogenicity factors (Ito et al, 2004;Johnson et al, 2000;Spassieva et al, 2002;Tanaka et al, 1999). Several secondary metabolites and proteins in A. brassicicola have been identified as toxins, such as depudecin (Wight et al, 2009), brassicenes (Hashimoto et al, 2009), Brassicicolin A (Pedras et al, 2009a), and two proteins (Oka et al, 2005;Otani et al, 1998).…”
Section: Introductionmentioning
confidence: 99%